Qualifications and Admission of Syarie Lawyers in Malaysia: A Comparative Analysis in Selected States - Muhammad Syahid Yusup; Muhammad Danial Mohd Arif; Muaz Ahmad Mustafa; Muhammad Harith Hakimi Zaharan; Mahfuzah Abdul Shukor; Nisar Mohammad Ahmad (Faculty of Syariah and Law, USIM, 2026)
The qualifications of Syarie lawyers play an important role in ensuring the implementation of justice and compliance with Sharia law in Syariah Courts. However, there are significant differences in the administration and regulations related to the qualifications and appointment of Syarie lawyers between states in Malaysia. This study aims to analyze the qualifications of Syarie lawyers in several selected states, identify the challenges that arise from these inconsistencies, and propose solutions to improve the Syarie lawyer administration system. This study uses a qualitative approach by collecting data through library research and interviewing stakeholders, such as Syarie lawyers and academics. The main data sources include books, journals, articles, Arabic books, and relevant state legal provisions. The study’s findings indicates that the qualifications, appointment procedures, and disciplinary actions against Syarie lawyers vary between states. This inconsistency not only creates confusion among prospective Syarie lawyers but also makes it difficult to coordinate efforts at the national level. In addition, this inconsistency affects the efficiency of the Syariah legal system, especially in ensuring high standards of professionalism and integrity among Syarie lawyers. This study proposes the drafting of a standardized rules relating to the qualifications and administration of Syarie lawyers in Malaysia. This rule should cover academic qualifications, appointment procedures, disciplinary control, and establishment of a regulatory body that coordinates all matters related to Syarie lawyers. This step is expected to increase the efficiency of the administration of Syariah law and strengthen the credibility of Syariah institutions in Malaysia.